Investigating the Effect of Gaze Cues and Emotional Expressions on the Affective Evaluations of Unfamiliar Faces - Landes, Todd Larson (PLoS One, 2016)
People look at what they are interested in, and their emotional expressions tend to indicate how they feel about the objects at which they look. The combination of gaze direction and emotional expression can therefore convey important information about people’s evaluations of the objects in their environment, and can even influence the subsequent evaluations of those objects by a third party, a phenomenon known as the emotional gaze effect. The present study extended research into the effect of emotional gaze cues by investigating whether they affect evaluations of the most important aspect of our social environment–other people–and whether the presence of multiple gaze cues enhances this effect. Over four experiments, a factorial within-subjects design employing both null hypothesis significance testing and a Bayesian statistical analysis replicated previous work showing an emotional gaze effect for objects, but found strong evidence that emotional gaze cues do not affect evaluations of other people, and that multiple, simultaneously presented gaze cues do not enhance the emotional gaze effect for either the evaluations of objects or of people. Overall, our results suggest that emotional gaze cues have a relatively weak influence on affective evaluations, especially of those aspects of our environment that automatically elicit affectively valenced reactions, including other humans.